2018
DOI: 10.4103/ija.ija_197_18
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of functionality of vocal cords using ultrasound before and after thyroid surgery: An observational study

Abstract: Background and Aims:The preservation of recurrent laryngeal nerve (RLN) is an essential part of thyroid surgery. The various methods to test the normal functionality of vocal cords (VCs) include direct visualisation under the fiber bronchoscope, indirect laryngoscopy, laryngeal muscles electromyography, computed tomography (CT), and magnetic resonance imaging (MRI). We aimed to assess the usefulness of ultrasound (USG) in the examination of VC morphology and movement.Methods:After Institutional Ethical Committ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…5 These results may be helpful as an important reference when evaluating diminished function of vocal folds caused by thyroid and parathyroid surgery, as well as other neuromuscular disorders (eg, Parkinson disease). [17][18][19] Our ultrasound elastography age-dependent findings for SWV and SWV ratio are consistent with observations by others that age-related FVF local tissue degeneration may lead to an increase of stiffness and decrease of function of FVF. 2,3 Having symmetry of FVF mechanical properties is essential for maintaining normal function of voice production, breathing, and swallowing.…”
Section: Discussionsupporting
confidence: 91%
“…5 These results may be helpful as an important reference when evaluating diminished function of vocal folds caused by thyroid and parathyroid surgery, as well as other neuromuscular disorders (eg, Parkinson disease). [17][18][19] Our ultrasound elastography age-dependent findings for SWV and SWV ratio are consistent with observations by others that age-related FVF local tissue degeneration may lead to an increase of stiffness and decrease of function of FVF. 2,3 Having symmetry of FVF mechanical properties is essential for maintaining normal function of voice production, breathing, and swallowing.…”
Section: Discussionsupporting
confidence: 91%
“…However, US is a cheaper and noninvasive diagnostic alternative to these methods. 20 There are studies in the literature showing the success of US in assessing VC function after thyroidectomy, with a varied diagnostic range (33%-100%). 9,11,14,21 One of the first studies was reported by Sidhu et al, 21 and although VCs from all the study patients were evaluated, the sensitivity was only 62%.…”
Section: Discussionmentioning
confidence: 99%
“…The VFDV was extensively investigated in many studies and the results were very promising regarding the practical implementation of this objective parameter. Dedecjus, Dubey and Kumar showed that the VFDV was significantly lower (<50% or <40 cm/s or 60 cm/s) after surgery resulting in VF injury [ 11 , 22 , 23 ]. In the literature, normal values ranged from 60–300 cm/s [ 12 ].…”
Section: Discussionmentioning
confidence: 99%